Desarrollo e implementación de un sistema de control de mantenimiento de equipos, mediante Java Server Faces-Glassfish y MySql con metodología Open up, para el departamneto técnico data market de Machala - 2012 - Zhañay Rueda, Hernán Darío (2013)
In the following study the technical feasibility of designing and implementing an Equipment Maintenance System for Enterprise Data Market and thus meet the need for the company to serve its customers in an easy way and encilla analyzed.